2011
DOI: 10.1002/pmic.201000424
|View full text |Cite
|
Sign up to set email alerts
|

Towards characterization of the glycoproteome of tomato (Solanum lycopersicum) fruit using Concanavalin A lectin affinity chromatography and LC‐MALDI‐MS/MS analysis

Abstract: The isolation and analysis of glycoproteins by coupling lectin affinity chromatography with MS has emerged as a powerful strategy to study the glycoproteome of mammalian cells. However, this approach has not been used extensively for the analysis of plant glycoproteins. As with all eukaryotes, N-glycosylation is a common post-translational modification for plant proteins traveling through the secretory pathway. Many such proteins are destined for the cell wall, or apoplast, where they play important roles in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 68 publications
1
64
0
1
Order By: Relevance
“…These proteins were identified by MALDI-TOF/TOF as putative ATPDIL1-4 (Arabidopsis thaliana protein disulfide isomerase-like 1-4) electron transporter (spot 1), protein disulphide isomerase (PDI) (spot 10), calreticulin 1 (CRT1) (spot 11), glycosyl hydrolase family 38 protein (GH 38) (spot 26), phantastica (spot 28), maturase k (spot 36), ATXR6 (Arabidopsis trithorax related protein 6) (spot 39), cysteine protease inhibitor (spot 43), con A precursor (spot 46) and an unnamed protein product (spot 47) ( Table 1). Out of these four proteins, GH 38 family protein (Catala et al 2011), PDI (Catala et al 2011), CRT1 (Komatsu et al 2009) and con A precursor (Sheldon and Bowles 1992) are reported to be glycosylated earlier. The identified proteins belong to vital physiological processes like protein targeting, redox homeostasis, organ identity, glycan metabolism and stress.…”
Section: Mass Spectrometric (Ms) Identification Of N-glycoproteins Rementioning
confidence: 99%
See 3 more Smart Citations
“…These proteins were identified by MALDI-TOF/TOF as putative ATPDIL1-4 (Arabidopsis thaliana protein disulfide isomerase-like 1-4) electron transporter (spot 1), protein disulphide isomerase (PDI) (spot 10), calreticulin 1 (CRT1) (spot 11), glycosyl hydrolase family 38 protein (GH 38) (spot 26), phantastica (spot 28), maturase k (spot 36), ATXR6 (Arabidopsis trithorax related protein 6) (spot 39), cysteine protease inhibitor (spot 43), con A precursor (spot 46) and an unnamed protein product (spot 47) ( Table 1). Out of these four proteins, GH 38 family protein (Catala et al 2011), PDI (Catala et al 2011), CRT1 (Komatsu et al 2009) and con A precursor (Sheldon and Bowles 1992) are reported to be glycosylated earlier. The identified proteins belong to vital physiological processes like protein targeting, redox homeostasis, organ identity, glycan metabolism and stress.…”
Section: Mass Spectrometric (Ms) Identification Of N-glycoproteins Rementioning
confidence: 99%
“…It contains thioredoxin (TRX) domain and acts as catalyst of disulfide bond formation in the oxidizing environment of endoplasmic reticulum stabilizing the tertiary and quaternary structure of protein (Gupta and Tuteja 2011). The presence of N-glycosylated form is reported in ripe tomato fruit by Catala et al (2011). PDI is involved in oxidation or reduction of disulfide bridges, cell adhesion, have chaperone and anti-chaperone activity and also act as a primary acceptor of peptides translocated into the ER (Noiva 1999;Onda 2013).…”
Section: Mass Spectrometric (Ms) Identification Of N-glycoproteins Rementioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two highly oxidized proteins involved in a wide range of biological processes were identified in ozone-treated rice using this method [127]. Phosphoproteome [128], glycoproteome, and secretome [129][130][131][132] are sub-categories of proteomics that require special staining and enrichment techniques. Post-translational modifications involved in gene expression regulations will be discussed in the Epigenomics section below.…”
Section: Proteomementioning
confidence: 99%